A Study on Teacher's Absenteeism and Performance in Underdeveloped Areas of West Kalimantan Province - Tasfirani, Tasfirani; Komari, Nurul; Rosnani, Titik (International Review of Management and Marketing, 2020)
This research aims at examining whether critical psychological states have an effect on teacher's absenteeism and performance in underdeveloped areas of West Kalimantan Province. The research employed a survey approach involving 200 participants which were selected from 3058 total population. The participants were selected using a two-stage sampling technique. Questionnaires were distributed as the primary instrument of the research. The data then were analyzed by SEM (WarpPLS) analysis. The results indicated that (1) critical psychological states had a significant effect on absenteeism, (2) critical psychological states had a significant effect on performance, (3) critical psychological states did not have a significant effect on performance when mediated by absenteeism, and (4) critical psychological states did not significantly affect teacher's performance in underdeveloped areas of West Kalimantan Province. Keywords: Critical psychological states, Absenteeism, Performance, Rural Areas JEL Classifications: E71, O18 DOI: https://doi.org/10.32479/irmm.10352